Desterritorialização e sofrimento em empregados que vivenciaram um processo de aquisição - Vieira, Henrique Gambaro (2011)
The acquisition operations have been ever more used as an organizational strategy for the companies to increase their actions to grow in the market which is more competitive and dynamic From the 90's when Brazil had abolished the market reserve together with the economical balance conquered in the years after, became the focus for foreign investments. One of the ways of investment conducted by foreign companies interested in joining the Brazilian market is through acquisition operations of foreign or Brazilian companies which already act in the national market. The acquisition operation herewith researched happened in 2008 in two financial foreign institutions that already had agencies and acted in the national market This operation can be understood as a process as one organization acquires another one or does not exist anymore with the operation. The buying organizations though demand the individuals from the acquired organization its form on management, its values and objectives. This way the exteriorizations process happens. When the worker notices the changes imposed by the new organization he sees his organizational spaces previously defined being changed making the individual adapt to the new space and relationship configurations presented. The leakage of the of the related contents which had been created by the members of the organization, which guided their relationships both practical and symbolic cause in the individuals related feelings in the lack of identity and values that previously existed among them and the organization. Through interviews conducted with employees who experienced the acquisition processes herewith researched between two financial institutions, we have tried to identify through content analysis the sufferings to identify which were the feelings that occurred with the interviewees, reflex of the exteriorization process provoked by the acquisition operation.For that purpose the snowball methodology was used which helped find individuals who had similar histories and experiences within the fusions operation. Five analysis categories were crated to better expose the processes of exteriorization experienced and point out the sufferings found within the fusion operation reflexes of those processes. The categories consist the contents related to the individual orientation, his values and recognition by the organization, the task achievement norms and the activities developed, the imposed investments, the imposed impeachments, the operational identity, health and strategies adopted by the employees to look for their new territories, The sufferings found inside the exposed categories were those related to frustration, the anxiety,, the restlessness, fear, despair and indignation. These feelings are pointed as possible indicators to suffering which can be related to use and devaluation felt by the employees and who changed their behavior, causing them to show inferior results they achieved before the process of acquisition. The knowledge of the reflexes of the acquisition process may help organizations that use their operations to created training programs and adaptations which meet their reflexes that may be counterproductive, keeping the organization away from its results.